PERAN KOMISARIS INDEPENDEN DALAM MEMODERASI RISIKO PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE - Luthfiana Nurjanah (2022)
The purpose of this study was to determine and analyze the role of independent commissioners in moderating corporate risk and sales growth on tax avoidance. This study uses a sample of manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 period. The sampling technique used in this study is purposive sampling with a sample acquisition of 80 companies. This study uses a quantitative method using panel data. The data analysis technique in this study used the classical assumption test, model selection test, multiple linear regression, and hypothesis testing. The results of this study indicate that the company's risk and sales growth do not have a significant effect on tax avoidance. then independent commissioners are not able to moderate the relationship between corporate risk and sales growth to tax avoidance